2018
DOI: 10.1080/21691401.2018.1536059
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of albendazole-loaded liposomes by supercritical carbon dioxide processing

Abstract: Supercritical fluid (SCF) technology offers a potential green alternative to organic solvent-based methods for drug formulation. Albendazole (ABZ) has promising anticancer activity when formulated to increase its cellular uptake. Herein, a static volume method was used to determine the solubility of ABZ in supercritical carbon dioxide (scCO 2) for the future development of such ABZ formulations. The solubility of ABZ in scCO 2 (250 bar, 37 C) was approximately 12 mg/100 mL. The extent of dissolution was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The free CHX was separated from the entrapped CHX by centrifugation [ 84 ]. The chitosomes were centrifuged at 4000× g and 4 °C for 30 min on the Biofuge Stratos centrifuge (Heraeus Instruments GmbH, Hanau, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The free CHX was separated from the entrapped CHX by centrifugation [ 84 ]. The chitosomes were centrifuged at 4000× g and 4 °C for 30 min on the Biofuge Stratos centrifuge (Heraeus Instruments GmbH, Hanau, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The observed data revealed the nanometric scale of the formulation with homogeneous dispersion of the liposomal formulation. Moreover, the negative value of the zeta potential may be attributed to the presence of fatty acids in lipids and possess anionic surface charge on liposomes, and the lower negative charge may enhance the drug entrapment in vesicle and enhanced cellular uptake in topical drug delivery. , …”
Section: Resultsmentioning
confidence: 99%
“…For this reason, curcumin was conjugated with GO and loaded into liposomes, which may improve the preformulation characteristics. , By combining both of them, they may show a synergistic response as antimicrobial. Liposomes have received a lot of interest in the topical drug delivery system because of their amphiphilic character, which makes them a superior penetration enhancer for the cutaneous route of administration than traditional formulations. Therefore, the objectives of this work were to achieve better antimicrobial actions over the CUR-loaded liposomes. As a result, the primary goal of this work was complex (CUR + GO complex) development, and its characterization was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…120 Fei et al 121 first produced vitamin D3 proliposomes using a SAS method in which liposomes were formed more simply through hydration. Macibool et al 122 reported that liposomes loaded with insoluble anticancer drugs using a SAS method exhibited promising anticancer activity when formulated to increase cellular uptake. With SAS technologies, hydrophilic and hydrophobic compounds can be trapped in vesicles simultaneously.…”
Section: Sustainable Nanomaterials Design and Synthesis For Molecule ...mentioning
confidence: 99%